Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Motor Yamaha Mio (Studi kasus pada PT. Harpindo Jaya Majapahit Semarang 2010) - Prasetyo, Olvie Okta; Prihatini, Apriatni Endang; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2012)
Customers buying behavior of a product is influenced by many factors. Every individual has the desire and taste different. Product quality is a factor that is very influential on purchase decisions, other than that there are many more factors that influence the buying behavior. This study aims to how much influence product quality, price, and promotion of their product purchasing decisions Yamaha Mio motorcycle and know the variables that have a dominant influence on purchase decisions Yamaha Mio motorcycle products to the public in the area of Semarang.Type is the type of research that used explanatory research. Samples were taken at 98 respondents that consumers who use Yamaha Mio motorcycle and make purchases at Harpindo Jaya branch of Majapahit. Determination of the sample with accidental sampling technique. Mechanical analysis of the data using linear regression analysis. Based on these results it can be concluded that: (a) there is a positive and significant effect on the variable quality of the product, (b) there is a positive and significant effect on the price variables, (c) there is a positive and significant impact on the promotion of the purchase decision variables Yamaha Mio. And who has the greatest influence is variable product quality. Hypothesis testing shows that the influence of product quality, price, and promotion of their purchasing decisions Yamaha Mio. The coefficient of determination for the variable quality of the product (X1), price (X2), and Promotion (X3) is 85.4% to the buying decision, while 14.6% Harpindo Jaya influenced other factors.PT. Harpindo Jaya should further enhance the promotion through electronic media and print media so that consumers always remember the product being offered. Prices were terjagkau and still maintain the quality must be maintained in order to remain in the interest of consumers.